A method for regulating galvanic corrosion of dual-phase Mg-Li alloy by combining gradient deformation with low-temperature annealing
Patent Information
- Application Number
- CN202411587289.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-11-08
AI Technical Summary
然而这种单相层的厚度通常较薄,仅为2~4微米,因此在腐蚀介质中容易被迅速消耗,导致其对双相镁锂合金腐蚀性能的提高效果有限
[0012]1、本发明使用机械碾压梯度变形与低温退火组合工艺,有效降低双相Mg-Li合金中β-Li相的位错密度,同时保持了α-Mg相对高位错密度,从而显著降低了α-Mg相的腐蚀电位,减少α-Mg相与β-Li相之间的腐蚀电位差异,有效减弱双相Mg-Li合金中的电偶腐蚀程度。
Smart Images

Figure CN119162520B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of materials science and technology, and specifically relates to a method for controlling galvanic corrosion of dual-phase Mg-Li alloys using a combination of gradient deformation and low-temperature annealing. Background Technology
[0002] Dual-phase magnesium-lithium alloys possess advantages such as low density, excellent plasticity, and high specific strength and specific stiffness, thus showing broad application potential in fields with high weight reduction requirements, such as aerospace, weaponry, and rail transportation. However, the corrosion potential of the α-Mg phase in dual-phase magnesium-lithium alloys is higher than that of the β-Li phase, causing them to form a galvanic corrosion pair in corrosive media such as water, aqueous solutions, and moisture, leading to preferential corrosion of the β-Li phase. This preferential corrosion not only increases the contact area between the alloy and the corrosive medium, thereby accelerating the corrosion rate, but may also trigger exfoliation corrosion of the α-Mg phase, further exacerbating the corrosion rate of the alloy. In summary, this preferential corrosion of the β-Li phase caused by the potential difference between the two phases significantly deteriorates the overall corrosion performance of the alloy. Currently, the main methods for reducing galvanic corrosion of dual-phase magnesium-lithium alloys include surface coating and surface fusion single-phase layer methods. The surface coating method involves coating the surface of the dual-phase magnesium-lithium alloy with a single-phase material (such as nickel deposition using electroplating technology) to isolate the dual-phase magnesium-lithium alloy from the corrosive medium, thereby preventing galvanic cell reactions between the α-Mg and β-Li phases. However, there is usually a significant difference in the coefficient of thermal expansion between the surface coating and the magnesium-lithium alloy. When temperature fluctuations cause alternating stress changes, the coating is prone to peeling off. Once the coating peels off, an galvanic corrosion pair will form between the exposed α-Mg phase and β-Li phase. Simultaneously, an even stronger galvanic corrosion pair often forms between the unpeeled coating and the exposed dual-phase magnesium-lithium alloy (because the coating material usually has a higher potential). Both of these situations exacerbate the degree of galvanic corrosion. In contrast, the surface-fused single-phase layer method (patent publication number CN 115094357) can transform the two-phase structure into a single-phase structure while maintaining the alloy composition, thereby eliminating the galvanic corrosion caused by the two-phase structure. However, the thickness of this single-phase layer is usually very thin, only 2–4 micrometers, and therefore it is easily and rapidly consumed in corrosive media, resulting in limited improvement on the corrosion resistance of dual-phase magnesium-lithium alloys. Summary of the Invention
[0003] The technical problem this invention aims to solve is to address the shortcomings of the prior art by providing a method for controlling galvanic corrosion in dual-phase Mg-Li alloys using a combination of gradient deformation and low-temperature annealing. This method utilizes a combination of mechanical rolling gradient deformation and low-temperature annealing to effectively reduce the dislocation density of the β-Li phase in the dual-phase Mg-Li alloy while maintaining a relatively high dislocation density in the α-Mg phase. This significantly reduces the corrosion potential of the α-Mg phase, decreases the corrosion potential difference between the α-Mg and β-Li phases, and effectively weakens the degree of galvanic corrosion in the dual-phase Mg-Li alloy. This provides more effective protection for the dual-phase magnesium-lithium alloy and solves the problems of easy peeling of surface coatings exacerbating corrosion and limited corrosion resistance of surface-fused single-phase layers in the prior art.
[0004] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is a method for controlling galvanic corrosion of dual-phase Mg-Li alloys using a combination of gradient deformation and low-temperature annealing, characterized in that the method includes the following steps:
[0005] Step 1: Fix the smooth and flat surface of the duplex Mg-Li alloy plate and determine the treatment area. Then, place the tungsten carbide ball on the surface of the duplex Mg-Li alloy plate and apply pressure in a direction perpendicular to the surface of the duplex Mg-Li alloy plate to control the tungsten carbide ball to perform reciprocating mechanical grinding in the treatment area.
[0006] Step 2: The dual-phase Mg-Li alloy plate after reciprocating mechanical grinding in Step 1 is subjected to low-temperature vacuum annealing to obtain a region with high dislocation density difference near the surface of the dual-phase Mg-Li alloy plate. In this region, the α-Mg phase has a relatively high dislocation density and the β-Li phase has a relatively low dislocation density.
[0007] For dual-phase alloys with well-defined compositions, the corrosion potential of each phase is related not only to unchangeable factors such as the chemical elements and crystal structure of each phase, but also to a controllable factor such as dislocation density. Specifically, an increase in dislocation density leads to a decrease in corrosion potential because dislocations, as high-energy linear crystal defects, can provide more active sites for chemical reactions, thereby accelerating the corrosion rate. Based on this, this invention weakens galvanic corrosion in dual-phase Mg-Li alloys by controlling the dislocation density of both phases. Specifically, this invention first uses tungsten carbide balls to apply pressure along the vertical direction to the treated area of the dual-phase Mg-Li alloy plate for reciprocating mechanical grinding. Through the accumulated plastic deformation and its transmission effect, the dislocation density gradually increases from the interior to the surface of the dual-phase Mg-Li alloy plate, forming a gradient deformation, such as... Figure 1As shown in Figure (a), the dislocation density of the β-Li phase in the dual-phase Mg-Li alloy is significantly reduced by low-temperature vacuum annealing, taking advantage of the lower melting point and easier recrystallization of the β-Li phase compared to the α-Mg phase. This results in a relatively low dislocation density in the β-Li phase, while the α-Mg phase retains a relatively high dislocation density, creating a region with a high dislocation density difference. In this region, the α-Mg phase has a relatively high dislocation density, while the β-Li phase has a relatively low dislocation density. Figure 1 As shown in the boxed area in Figure (b), this relatively high dislocation density reduces the corrosion potential of the α-Mg phase, thereby reducing the corrosion potential difference between the α-Mg phase and the β-Li phase, and thus weakening the degree of galvanic corrosion in the dual-phase Mg-Li alloy.
[0008] The above-mentioned method for controlling galvanic corrosion of duplex Mg-Li alloys using a combination of gradient deformation and low-temperature annealing is characterized in that the applied pressure in step one is 30 kgf to 40 kgf, and during the reciprocating mechanical grinding process, one cycle is defined as the tungsten carbide ball completing one mechanical grinding cycle across the entire treatment area, with a total of 20 to 30 reciprocating mechanical grinding cycles. This invention, by controlling the applied pressure and the reciprocating mechanical grinding cycle, gradually accumulates and transfers plastic deformation on the surface of the duplex Mg-Li alloy plate, ensuring the formation of gradient deformation.
[0009] The method described above for controlling galvanic corrosion of a dual-phase Mg-Li alloy using a combination of gradient deformation and low-temperature annealing is characterized in that the low-temperature vacuum annealing treatment in step two is performed at a temperature of 150℃ to 190℃ for a duration of 30 min to 60 min. This temperature and duration of the low-temperature vacuum annealing treatment allow the β-Li phase, which has undergone severe plastic deformation, to achieve a greater degree of recovery and recrystallization, thereby significantly reducing the dislocation density of the β-Li phase in the dual-phase Mg-Li alloy and allowing the α-Mg phase to retain a higher dislocation density. This effectively reduces the corrosion potential difference between the two phases and significantly reduces the degree of galvanic corrosion.
[0010] The above-mentioned method for controlling galvanic corrosion of dual-phase Mg-Li alloys using a combination of gradient deformation and low-temperature annealing is characterized in that the thickness of the region with high dislocation density difference in step two is 400 μm to 500 μm.
[0011] Compared with the prior art, the present invention has the following advantages:
[0012] 1. This invention uses a combination of mechanical rolling gradient deformation and low-temperature annealing to effectively reduce the dislocation density of the β-Li phase in the dual-phase Mg-Li alloy, while maintaining a relatively high dislocation density of the α-Mg phase. This significantly reduces the corrosion potential of the α-Mg phase, decreases the difference in corrosion potential between the α-Mg and β-Li phases, and effectively weakens the degree of galvanic corrosion in the dual-phase Mg-Li alloy.
[0013] 2. This invention regulates the galvanic corrosion between the α-Mg phase and β-Li phase in a dual-phase Mg-Li alloy by combining mechanical rolling gradient deformation with low-temperature annealing. It does not involve external coating materials and avoids the problem of coating peeling caused by the difference in thermal expansion coefficients between the coating and the dual-phase Mg-Li alloy substrate.
[0014] 3. The present invention forms a uniform corrosion zone with a thickness of 400μm to 500μm in the near-surface region of the dual-phase Mg-Li alloy plate. Its range is much larger than the thickness of conventional surface-fused single-phase layers (2 to 4 micrometers) and also significantly exceeds the thickness of commonly used protective coatings. Therefore, the present invention can provide more effective protection for dual-phase magnesium-lithium alloys.
[0015] 4. The operation method of the present invention is simple and low-cost, and does not require the use of any chemical reagents, thus avoiding environmental pollution.
[0016] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description
[0017] Figure 1 This is a graph showing the trend of two-phase dislocation density as a function of plate depth during reciprocating mechanical grinding and low-temperature vacuum annealing of the duplex Mg-Li alloy plate of the present invention.
[0018] Figure 2 This is a morphology diagram of the dual-phase Mg-Li alloy after being subjected to a combination of reciprocating mechanical grinding and low-temperature vacuum annealing in Example 1 of the present invention. Detailed Implementation
[0019] Example 1
[0020] This embodiment includes the following steps:
[0021] Step 1: Fix the smooth and flat surface of the duplex Mg-Li alloy plate and determine the treatment area. Then, place the tungsten carbide ball on the surface of the duplex Mg-Li alloy plate and apply a pressure of 30 kgf in a direction perpendicular to the surface of the duplex Mg-Li alloy plate. Control the tungsten carbide ball to perform reciprocating mechanical grinding in the treatment area. During the reciprocating mechanical grinding process, one cycle is defined as the tungsten carbide ball completing one mechanical grinding in the entire treatment area. A total of 30 cycles of reciprocating mechanical grinding are performed.
[0022] Step 2: The dual-phase Mg-Li alloy plate after reciprocating mechanical grinding in Step 1 is subjected to low-temperature vacuum annealing at 150℃ for 30 minutes to obtain a region with a high dislocation density difference of 400μm in thickness near the surface of the dual-phase Mg-Li alloy plate. In this region, the α-Mg phase has a relatively high dislocation density and the β-Li phase has a relatively low dislocation density.
[0023] Figure 2 Figure 1 shows the morphology of the dual-phase Mg-Li alloy after reciprocating mechanical grinding and low-temperature vacuum annealing in Example 1 of this invention. Figure (a) is a cross-sectional metallographic morphology of the dual-phase Mg-Li alloy after regulation, and Figure (b) is a three-dimensional morphology of the dual-phase Mg-Li alloy after regulation. As can be seen from Figure (a), there is a uniform corrosion zone with a depth of about 400 μm between a depth of 350 μm and a depth of nearly 800 μm in the dual-phase Mg-Li alloy after regulation, along the direction from the surface to the substrate. There is no obvious corrosion undulation contrast between the α-Mg phase and the β-Li phase in this uniform corrosion zone, as shown by the area between the dashed lines in Figure (a). At the same time, as can be seen from Figure (b), the heights of the two phases in this uniform corrosion zone are very close, indicating that the α-Mg phase and the β-Li phase have almost the same corrosion rate after regulation. In addition, this uniform corrosion zone has the highest height compared with the adjacent areas on the left and right, indicating that this uniform corrosion zone has the lowest corrosion rate, which shows that the method of this invention can significantly improve the corrosion resistance of the dual-phase magnesium-lithium alloy.
[0024] Example 2
[0025] This embodiment includes the following steps:
[0026] Step 1: Fix the smooth and flat surface of the duplex Mg-Li alloy plate and determine the treatment area. Then, place the tungsten carbide ball on the surface of the duplex Mg-Li alloy plate and apply a pressure of 40 kgf in a direction perpendicular to the surface of the duplex Mg-Li alloy plate. Control the tungsten carbide ball to perform reciprocating mechanical grinding in the treatment area. During the reciprocating mechanical grinding process, one cycle is defined as the tungsten carbide ball completing one mechanical grinding in the entire treatment area. A total of 20 cycles of reciprocating mechanical grinding are performed.
[0027] Step 2: The dual-phase Mg-Li alloy plate after reciprocating mechanical grinding in Step 1 is subjected to low-temperature vacuum annealing at 190℃ for 60 minutes to obtain a region with a high dislocation density difference of 500μm in thickness near the surface of the dual-phase Mg-Li alloy plate. In this region, the α-Mg phase has a relatively high dislocation density and the β-Li phase has a relatively low dislocation density.
[0028] Upon testing, it was found that the region with a high dislocation density difference and a thickness of 500 μm near the surface of the dual-phase Mg-Li alloy plate in this embodiment is a uniform corrosion zone with high corrosion resistance.
[0029] Example 3
[0030] This embodiment includes the following steps:
[0031] Step 1: Fix the smooth and flat surface of the duplex Mg-Li alloy plate and determine the treatment area. Then, place the tungsten carbide ball on the surface of the duplex Mg-Li alloy plate and apply a pressure of 35 kgf in a direction perpendicular to the surface of the duplex Mg-Li alloy plate. Control the tungsten carbide ball to perform reciprocating mechanical grinding in the treatment area. During the reciprocating mechanical grinding process, one cycle is defined as the tungsten carbide ball completing one mechanical grinding in the entire treatment area. A total of 25 reciprocating mechanical grinding cycles are performed.
[0032] Step 2: The dual-phase Mg-Li alloy plate after reciprocating mechanical grinding in Step 1 is subjected to low-temperature vacuum annealing at 170℃ for 45 minutes to obtain a region with a high dislocation density difference of 450μm in thickness near the surface of the dual-phase Mg-Li alloy plate. In this region, the α-Mg phase has a relatively high dislocation density and the β-Li phase has a relatively low dislocation density.
[0033] Upon testing, it was found that the region with a high dislocation density difference and a thickness of 450 μm near the surface of the dual-phase Mg-Li alloy plate in this embodiment is a uniform corrosion zone with high corrosion resistance.
[0034] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention in any way. Any simple modifications, alterations, and equivalent changes made to the above embodiments based on the inventive essence shall still fall within the protection scope of the present invention.
Claims
1. A method for controlling galvanic corrosion of a dual-phase Mg-Li alloy using a combination of gradient deformation and low-temperature annealing, characterized in that, The method includes the following steps: Step 1: Fix the smooth and flat surface of the duplex Mg-Li alloy plate and determine the treatment area. Then, place the tungsten carbide ball on the surface of the duplex Mg-Li alloy plate and apply pressure in a direction perpendicular to the surface of the duplex Mg-Li alloy plate to control the tungsten carbide ball to perform reciprocating mechanical grinding in the treatment area. Step 2: The dual-phase Mg-Li alloy plate after reciprocating mechanical grinding in Step 1 is subjected to low-temperature vacuum annealing to obtain a region with high dislocation density difference near the surface of the dual-phase Mg-Li alloy plate. In this region, the α-Mg phase has a relatively high dislocation density and the β-Li phase has a relatively low dislocation density.
2. The method for controlling galvanic corrosion of a dual-phase Mg-Li alloy using a combination of gradient deformation and low-temperature annealing according to claim 1, characterized in that, The pressure applied in step one is 30 kgf to 40 kgf. During the reciprocating mechanical grinding process, one cycle is defined as the tungsten steel ball completing one mechanical grinding cycle in the entire processing area. A total of 20 to 30 cycles of reciprocating mechanical grinding are performed.
3. The method for controlling galvanic corrosion of a dual-phase Mg-Li alloy using a combination of gradient deformation and low-temperature annealing according to claim 1, characterized in that, The low-temperature vacuum annealing process described in step two is performed at a temperature of 150℃ to 190℃ for a duration of 30 min to 60 min.
4. The method for controlling galvanic corrosion of a dual-phase Mg-Li alloy using a combination of gradient deformation and low-temperature annealing according to claim 1, characterized in that, The thickness of the region with high dislocation density difference mentioned in step two is 400 μm to 500 μm.
Citation Information
Patent Citations
Method for fusing single-phase layer on surface of dual-phase Mg-Li alloy plate at room temperature
CN115094357A
Magnesium-lithium alloy and manufacturing method therefor
JP2020002405A